Stem Cell Tracking with Nanoparticles for Regenerative Medicine Purposes: An Overview - Lisa Accomasso; Clara Gallina; Valentina Turinetto; Claudia Giachino (Stem Cells International)
Accurate and noninvasive stem cell tracking is one of the most important needs in regenerative medicine to determine both stem cell destinations and final differentiation fates, thus allowing a more detailed picture of the mechanisms involved in these therapies. Given the great importance and advances in the field of nanotechnology for stem cell imaging, currently, several nanoparticles have become standardized products and have been undergoing fast commercialization. This review has been intended to summarize the current use of different engineered nanoparticles in stem cell tracking for regenerative medicine purposes, in particular by detailing their main features and exploring their biosafety aspects, the first step for clinical application. Moreover, this review has summarized the advantages and applications of stem cell tracking with nanoparticles in experimental and preclinical studies and investigated present limitations for their employment in the clinical setting.